Glandular and extraglandular expression of the Fas-Fas ligand and apoptosis in patients with Sjögren's syndrome - Matsumura, R; Umemiya, K; Kagami, M; Tomioka, H; Tanabe, E; Sugiyama, T; Sueishi, M; Nakajima, A; Azuma, M; Okumura, K; Sumida, T (Clinical and experimental rheumatology, 1998)
To evaluate the role of Fas-Fas ligand system-mediated apoptosis in the sialoadenitis and interstitial nephritis of Sjögren's syndrome. The expression of Fas antigen and Fas ligand in sialoadenitis and interstitial nephritis was examined by immunoperoxidase staining and the reverse transcriptase-polymerase reaction (RT-PCR) in patients with Sjögren's syndrome and in normal subjects. The appearance of DNA strand breaks during apoptosis was detected in the tissue by DNA nick end labeling methods. In patients with severe sialoadenitis, Fas antigen was strongly expressed on the ductal epithelial cells. In contrast, Fas antigen was not seen in the minor salivary glands of normal subjects nor in patients with mild sialoadenitis. In patients with massive mononuclear cell infiltration, some of the infiltrating cells showed the Fas ligand. In patients with interstitial nephritis associated with Sjögren's syndrome, Fas was expressed on the tubular epithelial cells, while such expression was not observed in control subjects without interstitial nephritis. In the patients with interstitial nephritis, some of the infiltrating cells showed the Fas ligand. Apoptotic changes were observed in the ductal epithelial cells, tubular epithelial cells and some infiltrating cells by DNA nick end labeling methods. mRNA for the Fas antigen and Fas ligand was found to be expressed in the labial salivary glands from all SS patients by RT-PCR. The findings of this study suggest that the Fas-Fas ligand system may play a role in the pathogenesis of the sialoadenitis and interstitial nephritis of Sjögren's syndrome.